The economic impact of circulating tumor-tissue modified HPV DNA for the post-treatment surveillance of HPV-driven oropharyngeal cancer: A simulation. (March 2022) - Ward, Matthew C.; Miller, Jacob A.; Walker, Gary V.; Moeller, Benjamin J.; Koyfman, Shlomo A.; Shah, Chirag
Highlights: Circulating tumor-tissue modified HPV DNA can detect oropharynx cancer but may be costly. In this model, the increased cost is approximately $9082 per patient over 5 years. Multiple scenarios were investigated detailing the use of ctHPVDNA. Abstract: Purpose: Following treatment of HPV-driven oropharynx cancer, surveillance nasopharyngoscopy and imaging are often performed but are expensive and frequently ineffective. A novel plasma circulating tumor-tissue modified viral HPV DNA (TTMV-HPV-DNA) assay accurately detects recurrences. We modeled the cost of the new assay. Methods: We designed and validated a partitioned survival model which replicated the results of the RTOG 1016 study and calculated cumulative surveillance costs from the payer's perspective. Two strategies were considered: a standard of routine endoscopy with imaging as needed and an alternative strategy which omitted scopes and imaging but obtained serial TTMV-HPV-DNA samples. No difference in effectiveness (QALY or LY) was assumed in the base case. A 5-year horizon was used, costs were reported in 2020 U.S. dollars discounted by 3%. Seven scenarios tested model assumptions and practice variation. Deterministic and probabilistic sensitivity analyses assessed parameter uncertainty. Results: In the base case, at the list TTMV-HPV-DNA price, the cumulative cost of surveillance was $11, 674 for the standard strategy and $20, 756 for the TTMV-HPV-DNA strategy (+$9082 over 5 years). Probabilistic sensitivity analysis demonstrated the cost difference ranged from $4917-$12, 047. The TTMV-HPV-DNA strategy was most likely to be either cost saving or cost-effective if future data demonstrate small improvements in quality or quantity of life (approximately 33 quality-adjusted life-days), if the assay reduces utilization of imaging, and if the periodicity of TTMV-HPV-DNA draws could be reduced from that on clinical trials. Conclusions: This data informs providers seeking to design more accurate, accessible, and economical post-treatment surveillance strategies.